2006
DOI: 10.5650/jos.55.585
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidation Activity of Various Rice Brans

Abstract: The original concept of rice brands resulted from consumer demand for a quality improvement in rice. In the Edo era, when rice was identified with the locality of its production, rice types such as Sanuki-mai and Omi-mai were given the brand name of their region. Rice brands and the areas of their distribution were thus named according to the brands of the prefecture. In 1970 the current naming system and distribution system were established to ensure a smooth distribution of rice. Since 1979 the government ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In the present study, a total of 10 components were isolated of which, cycloartenyl ferulate, 24-methylenecycloartanyl ferulate, campesteryl ferulate and sitosteryl ferulate were identified as the major components. Interestingly, herein analysis time was shortened to 40Âminutes compared with previous report of 60Âminutes and the peak retention time ranged between 15–30Âminutes [38,40,41]. …”
Section: Resultsmentioning
confidence: 68%
“…In the present study, a total of 10 components were isolated of which, cycloartenyl ferulate, 24-methylenecycloartanyl ferulate, campesteryl ferulate and sitosteryl ferulate were identified as the major components. Interestingly, herein analysis time was shortened to 40Âminutes compared with previous report of 60Âminutes and the peak retention time ranged between 15–30Âminutes [38,40,41]. …”
Section: Resultsmentioning
confidence: 68%
“…That is, the induction period for the oxidation of ML with DRB from 96-98% and 98-100% yield was prolonged. It has been reported that the rice bran of 98-100% milling yield, which is not defatted, exhibits the highest radicalscavenging activity in the bran samples of Nihonbare rice from the different milling yields (88-100%) and a-tocopherol and coryzanol are the main antioxidants in the bran (Fujita et al, 2006). Similarly to these lipophilic antioxidants, hydrophilic compounds having antioxidative activity, such as various phenolic compounds, in the branny layer, would be in outer branny layers to defend the endosperm against the external oxidative stress (Asada, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Rice bran is a major by-product obtained from the milling process. Lipids extracted from rice bran include antioxidative compounds, such as tocopherols and c-oryzanol (Fujita, Masumoto, Kawakami, Mikami, & Nomura, 2006), and they have been used as food material with a beneficial influence on health. On the other hand, defatted rice bran (DRB) with these lipophilic components removed is not used enough, despite its potential availability.…”
Section: Introductionmentioning
confidence: 99%
“…Fresh rice bran has been shown to contain various nutritional compounds, including vitamins and oils (Iwai and Yokomizo, 1967;Shimizu et al, 1957;Kato et al, 1981), as well as exhibiting various physiological functions (NaraiKanayama et al, 2007;Saito et al, 1992;Kaneda et al, 2006;Fujita et al, 2006;Hiwatari et al, 2010;Arimura et al, 2003;Inokuchi et al, 2003;Aoe et al, 1989;Ayano et al, 1980;Naito et al, 2003), such as angiotensin I-converting enzyme (ACE) inhibitory activity (Narai-Kanayama et al, 2007;Saito et al, 1992), and antioxidative effects (Kaneda et al, 2006;Fujita et al, 2006). Fresh rice bran contains about 13% crude protein (w/w) on a wet basis (Ministry of Education, Culture, Sports, Science and Technology, 1982).…”
Section: Introductionmentioning
confidence: 99%